Whose God Rules?: Is the United States a Secular Nation or a Theolegal Democracy? - Walker, Rev. Nathan C. (Palgrave Macmillan, 2011)
This book demonstrates that the United States, whether we like it or not, is a theolegal nation - a democracy that simultaneously guarantees citizens the right to free expression of belief while preventing the establishment of a state religion.